“Efecto de Quitomax sobre el crecimiento y producción del cultivo de pepino (Cucumis sativus L.)” - Calderón Álvarez, Bryan Vicente (2021)
Cucumber cultivation is generally establishhed under a convetional production system in which it is noruishd with fertilizers of synthetic origin, but due to its side effexts, it is necesary to explore more evironmentally friendly production alternatives. The present research aimed to evalute the effect of quitomax on the growth and production of the cucumber (Cucumis sativus L.) crop. The wash carried out at the "Cinco hermanas" farm, located in the Sonia María area at km 16.5 of the Buena Fe-Santo Domingo de los Tsáchilas road. A randomized complete block design (DBCA) was used with six tretments in three repetitions.....................................